﻿Two new species of Varicus from Caribbean deep reefs, with comments on the related genus Pinnichthys (Teleostei, Gobiidae, Gobiosomatini, Nes subgroup) - Katlyn M. Fuentes; Carole C. Baldwin; D. Ross Robertson; Claudia C. Lardizábal; Luke Tornabene (ZooKeys, 2023)
Tropical deep reefs (~40–300 m) are diverse ecosystems that serve as habitats for diverse communities of reef-associated fishes. Deep-reef fish communities are taxonomically and ecologically distinct from those on shallow reefs, but like those on shallow reefs, they are home to a species-rich assemblage of small, cryptobenthic reef fishes, including many species from the family Gobiidae (gobies). Here we describe two new species of deep-reef gobies, Varicus prometheus sp. nov. and V. roatanensis sp. nov., that were collected using the submersible Idabel from rariphotic reefs off the island of Roatan (Honduras) in the Caribbean. The new species are the 11th and 12th species of the genus Varicus, and their placement in the genus is supported by morphological data and molecular phylogenetic analyses. Additionally, we also collected new specimens of the closely-related genus and species Pinnichthys aimoriensis during submersible collections off the islands of Bonaire and St. Eustatius (Netherland Antilles) and included them in this study to expand the current description of that species and document its range extension from Brazil into the Caribbean. Collectively, the two new species of Varicus and new records of P. aimoriensis add to our growing knowledge of cryptobenthic fish diversity on deep reefs of the Caribbean.